Egg marks the spot : a Skunk and Badger story - Timberlake, Amy (Timberlake, Amy. Skunk and Badger (Series), 2021)
"Roommates Skunk and Badger head out on a rock-finding expedition that becomes much more dangerous than they ever expected"--